Immunohistochemical and morphological changes associated with hepatic damage in lead acetate-induced toxicity and mitigatory properties of naringin in cockerel chicks (Nigerian Journal of Physiological Sciences, 2023)
Lead (Pb) toxicity constitutes a major health hazard to both humans and animals especially in the developing countries. It is a ubiquitous environmental contaminant found in the air essentially because of unregulated mining and other industrial activities. Lead can be found naturally in the soil thus, contaminating crops for human and animal food, as well as run-off water and air pollution. Intensively and extensively reared domestic chickens are exposed to contamination via inhalation and ingestion of contaminated food materials. Naringin, a product from citrus plant has been described to possess excellent metal chelating ability. Naringin is rich in flavonoid with attendant antioxidant, anti-autophagy, anti-inflammatory, hepatoprotective and cardio-nephroprotective properties. This study was conducted to investigate the hepatoprotective and modulation of oxidative stress in commercial cockerel chickens by Naringin. Thirty-six commercial cockerel chickens were randomly assigned into six groups A-F of six birds each viz: Group A served as control group while groups B, C, and D received Lead acetate at 300 ppm via drinking water continuously till the end of the experiment. In addition, groups C and D were treated with Naringin at 80 mg/kg and 160mg/kg, respectively, via oral gavage for 8 weeks. Groups E and F were administered naringin only at 80mg/kg and 160mg/kg respectively for eight weeks. Pb toxicity induced degenerative changes in the histological sections as well as, higher expression of hepatic caspase 3 as shown by immunohistochemistry. There was increased oxidative stress markers (H2O2, MDA) and depletion of the antioxidant defense system markers SOD, GPx, GSH, and GST. It concluded that Co- treatment with Naringin ameliorated oxidative stress, enhanced antioxidant defense system, reduced the expression of hepatic caspase 3 thus, offering protection against lead acetate-induced derangements in the liver of commercial cockerel chickens
Keywords: Lead acetate; Naringin; Oxidative stress; immunohistochemistry